Aberrant microRNA expression in peripheral plasma and mononuclear cells as specific blood-based biomarkers in schizophrenia patients. Issue 3 (March 2015) - Sun, Xin-yang; Lu, Jim; Zhang, Liang; Song, Hong-tao; Zhao, Lin; Fan, Hui-min; Zhong, Ai-fang; Niu, Wei; Guo, Zhong-min; Dai, Yun-hua; Chen, Chao; Ding, Yan-fen; et al.
Abstract Findings from multiple studies on microRNA (miRNA) expression profiling in schizophrenia patients have produced conflicting results. In order to investigate miRNA as specific biomarkers in the peripheral plasma and peripheral blood mononuclear cells (PBMC) of schizophrenia patients, expression levels of the nine most frequently reported schizophrenia-associated miRNA (miR-30e, miR-34a, miR-181b, miR-195, miR-346, miR-432, miR-7, miR-132 and miR-212) were examined in the peripheral plasma and PBMC in 25 schizophrenia patients and 13 healthy controls using quantitative real-time reverse transcription polymerase chain reaction. We observed significantly increased expressions of miR-132, miR-195, miR-30e and miR-7 in plasma samples (p < 0.05 to p < 0.001), and miR-212, miR-34a and miR-30e in PBMC samples (p < 0.05 to p < 0.01). Receiver operating characteristic curve analysis revealed that the area under the curve (AUC) of miR-30e in plasma was 0.767 (95% confidence interval [CI] 0.608–0.926) with sensitivity and specificity of 90.90% and 60.00% respectively, and the AUC of miR-30e in PBMC was 0.756 (95% CI 0.584–0.929) with sensitivity and specificity of 81.80% and 68.00%, respectively. Logistic regression analysis demonstrated that miR-30e in plasma was more sensitive to differentiate schizophrenia patients from normal controls than miR-30e in PBMC. Our findings indicate that miRNA expression is more significant in plasma than in PBMC, and suggest that miR-30e in plasma may be a more sensitive biomarker for schizophrenia diagnosis, although its aberrant expression can be detected in both plasma and PBMC.